Nephroprotective and hepatoprotective effects of terminalia ivorensis a. chev. ethanolic stem bark extract on sprague dawley rats - Aliu, Moomin (2016)
A thesis submitted in fulfillment of the requirements for the degree of Master of Philosophy In the Department of Pharmacology Faculty of Pharmacy and Pharmaceutical Sciences.